El leon, la bruja, y el ropero - Lewis, C. S. (Clive Staples), 1898-1963; Baynes, Pauline (New York : HarperTrophy, 2002)
Four English schoolchildren find their way through the back of a wardrobe into the magic land of Narnia and assist Aslan, the golden lion, to triumph over the White Witch, who has cursed the land with eternal winter.
Accelerated Reader
Keywords: Fantasy fiction -- Juvenile literature; Novela fantastica -- Literatura juvenil